Cayenniola albaserrata n. sp., a geographical relict from a Brazilian hotspot of subterranean biodiversity and the first troglobitic Priodesmini (Polydesmida: Chelodesmidae: Chelodesminae) - Bouzan, Rodrigo S.; Means, Jackson C.; Ivanov, Kaloyan; Ferreira, Rodrigo L.; Brescovit, Antonio D.; Iniesta, Luiz F.m. (Zootaxa, 2024)
A new troglobitic species of Chelodesmidae, Cayenniola albaserrata n. sp., from the Água Clara cave system, Caatinga Domain, Bahia, Brazil is described. The new species is only the sixth known troglobitic chelodesmid, the first troglobitic species in the Priodesmini, and the first member of the tribe recorded from the state of Bahia. Unique among the Priodesmini, male C. albaserrata n. sp. possess greatly elongated pre-gonopodal tarsal claws and differ from the only congener, Cayenniola styliger (Jeekel, 1963), by a combination of gonopodal and somatic characters including classical troglomorphic traits such as a nearly unpigmented body and remarkably long antennae, legs, and tarsal claws. Cayenniola styliger is only known from the type locality in the Amazon rainforest of coastal French Guiana, suggesting that C. albaserrata n. sp. may represent a relictual species from the Caatinga Domain of Brazil. We provide ecological notes and evaluate the potential threats to the habitat of C. albaserrata n. sp., considering both the subterranean environment and the surrounding areas.